Functional outcome of plating for displaced middle third clavicle fractures in adults - Sitaula, Jyoti; Regmi, Ananda Prasad; Prajapati, Akesh; Thapa, Suresh Bahadur; Sharma, Bishnu Dev; Shrestha, Sujit Raj; Pant, Pujan; Rijal, Sanjeeb (Journal of Chitwan Medical College, 2018)
Introduction: Clavicle fractures are the common fractures around the shoulder. Conservative treatment is associated with higher incidence of nonunion. We conducted this study to assess the functional outcome of plating for displaced middle third clavicle fractures. Methods: This prospective study included 60 patients with displaced middle third clavicle fractures from April 2016 to March 2017. Fixation was done with a 3.5 mm reconstruction plate placed at the superior surface of the clavicle. Patients were followed-up for a minimum of one year. Functional outcome was assessed using Constant shoulder score. Results: There were 48 male and 12 female patients with a mean age of 33.17 years (range 18-74 years). The average follow-up period was 17.82 months. All fractures united at an average of 5.35 months. The mean Constant score at final follow-up was 89.12. There were two superficial infections and three implant failures. Conclusion: We conclude that treatment of displaced middle third clavicle fracture with plate gives good results.